Perrotta Affective Dependence Questionnaire (PAD-Q): Clinical framing of the affective-sentimental relational maladaptive model - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Starting from the concept of "affective dependence", this work has shown that this nosography cannot be reduced to a categorization in the list of behavioral dependencies, even if it has in common clinical and neurobiological aspects that could be misleading. In fact, the dependent manifestation is nothing more than a symptom that from time to time represents a specific element in various personality disorders, becoming the central focus of dependent personality disorder. The analytical approach must, therefore, be multidimensional, precisely to better understand all aspects of affective dependence and how it colors the manifested disorder from time to time. From affective dependence to personality disorders, in relation to the dynamics of human bonding, to the implications determined by attachment theory, in a framework of diagnostic transversality, to the best possible therapy, always integrated between psychopharmacology and psychotherapy. The Perrotta Affective Dependence Questionnaire (PAD-Q), with 35 items, on a 0-5 scale, aims to study the phenomenon of "affective dependence", defining it instead as a maladaptive model of the affective-sentimental relationship of a couple, which involves the establishment or persistence of a clinically significant bond, lasting at least six months and characterized by a functional impairment of the relational area, the emotional area and the somatic area.